HUBUNGAN TINGKAT KEPATUHAN KONSUMSI OBAT KELASI BESI DENGAN KADAR FERRITIN PADA PASIEN THALASSEMIA ANAK DI RSUD DR. MOEWARDI - Tabita Desna Shadiar Hawa; Muhammad Riza; Diah Lintang Kawuryan (Universitas Duta Bangsa Surakarta, 2023)
Thalassemia is a hereditary hemolytic disease caused by mutations in the hemoglobin synthesis chain. Transfusion-dependent thalassemia patients require iron chelation therapy to prevent complications of iron overload. Adherence with regular iron chelation consumption is important for good survival, reducing morbidity and mortality in thalassemia patients. This research is an analysis of an observational study with a cross-sectional approach. This research was conducted at RSUD Dr. Moewardi. The subjects of this study were pediatric thalassemia patients who were taking deferiprone iron chelating drugs. The sample was taken using purposive sampling method, by analysing medical record data and the MMAS-8 questionnaire. Data were examined using the chi-square test with the SPSS application. Results: There were 56 subjects to be analyzed consisting of 23 males and 33 females. Based on the chi-square test, there was a significant relationship between consumption of iron chelating drugs and ferritin levels with p = 0.026. In addition, another study was conducted using the chi-square test regarding nutritional status and duration of thalassemia illness on ferritin levels. The results obtained were p value = 0.977 for the relationship between nutritional status and p value = 0.977 for the long duration of thalassemia illness. It can be concluded that both of them have no significant effect on ferritin levels. Adherence with taking iron chelating drugs has a significant relationship to ferritin levels in thalassemia patients.